FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KANTOR PELAYANAN PERBENDAHARAAN NEGARA SURAKARTA - Danan Dwi Mulyono (Master of Public Administration, Universitas Slamet Riyadi, 2014)
The objective of this research is to describe factors affecting the employeesperformance of the State Treasure Office in Surakarta. Three hypotheses areformulated. First hypothesis is that leadership factor, human resource factor,and organizational culture factor, partially influence the performance of theemployees of State Treasure Office in Surakarta. The second hypothesis is thatthe three factors influencing the performance of the employees of the Statetreasure Office are interrelated. The third hypothesis is that leadership factor,human resource factor, and organizational culture factor simultaneously affectthe performance of the performance of the employees of the State Treasure.Research was conducted in Surakarta. Amount of sixty respondents wasselected. Questionnaire and documentation data collecting techniques wereemployed. Simple as well as multiple regression and correlation are used toanalyse data. Research result shows that the first hypothesis is supported(significant at 0,000 level). The second hypothesis is also upheld (significant at0.000 level). The third hypothesis is also accepted (significant at 0.008 level).Result of data analysis suggest that there are intercorrelation between the threevariables predicted having influence the performance of the employees of theState Treasury Office.Key words: Leadership; human resource, organizational culture; performance of theemployee